Organizational Attractiveness, Social Media, dan Corporate Reputation sebagai Mediasi Employer Branding terhadap Intention to Apply For a Job - Abanan, Muchammad Zuhri Ramadhani; Moko, Wahdiyat; Firanda, Brilian Setia; Aini, Maya Faridhotul (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: To determine the direct influence of employer branding, social media, organizational attractiveness, and corporate reputation on the intention to apply for a job. Additionally, the study aims to investigate the indirect effect of employer branding on the intention to apply for a job through social media, organizational attractiveness, and corporate reputation. Research methodology: The research was conducted on university alumni in Malang. It employed a survey method using a questionnaire as the data collection tool. The study involved 210 respondents from both public and private universities in Malang. A Likert scale ranging from 1 to 5 was used for measurement. The analysis was performed using Structural Equation Modeling (SEM) with PLS software. Results: The study reveals that employer branding significantly boosts job application intentions, with social media serving as a mediator that amplifies this impact. Organizational attractiveness, emphasizing product quality and workplace environment, emerges as the most influential factor. Corporate reputation also positively influences job application intentions and mediates the relationship with employer branding. These interconnected factors offer valuable guidance for enhancing recruitment strategies. Limitations: The study has limitations, including its focus university alumni in Malang. Contribution: This research can be seen from several aspects that are relevant to both theory and practice in the fields of human resource management and organizational marketing, particularly related to employer branding and recruitment.